Study of charged Lepton Flavor Violation in electron muon interactions - Ran Ding; Jingshu Li; Meng Lu; Zhengyun You; Zijian Wang; Qiang Li (Journal of High Energy Physics)
Abstract With the improvement of muon acceleration technology, it has received great interests to exploit high-energy muon beams for collision or target experiments. We investigate the possible charged Lepton Flavor Violation (cLFV) processes mediated by an extra massive neutral gauge boson Z′ in electron muon interactions, either at a proposed electron muon collider or in a fixed target experiment with high-energy muon beam hitting electrons in the target. Based on Monte Carlo calculations and fast detector simulations, we study in detail the signal and possible backgrounds, giving the sensitivity results of cLFV signals at the 90% confidence level. Compared with the current and prospective limits set by other experiments, electron muon interactions demonstrate significant advantages in the cLFV coupling strength sensitivity with τ in the final states. In addition, a special cLFV coupling combination, λ eμ × λ μμ , can also be probed in our proposal.